An hourglass model for conceptualising stigma in infectious disease outbreaks - Amy Paterson; Benjamin Jones; Olive Kabajaasi; Ashleigh Cheyne; Harun Tulunay; Kkunsa Hadson; Jeni Stolow; Nina Gobat; Piero Olliaro; Amanda Rojek (Scientific Reports)
Abstract Stigma is widely observed during (re)emerging infectious disease outbreaks, contributing to psychological distress, social isolation, and care-seeking hesitancy. Despite this, it is often inadequately addressed in public health responses, partly due to the lack of a fit-for-purpose approach. The objective of this study was to develop a conceptual model to facilitate structured consideration of stigma during (re)emerging disease outbreaks. We conducted 34 in-depth interviews with international stakeholders across 25 outbreak-prone diseases, including emergency response leaders, frontline responders, researchers, and community advocates. We analysed transcripts using thematic analysis, integrating insights from social and behavioural theories to refine the model. We introduce the hourglass stigma model, a theory-informed conceptualisation of stigma in outbreaks. The model consists of five domains (major themes): context, thoughts, emotions, manifestations, and impact. Within each domain there are key considerations, such as the influence of response measures on concealability (context), the association of certain diseases with ‘dirtiness’ due to hygiene-dominant messaging (thoughts), the negative effects of fear-based appeals (emotions), the enactment of stigma due to unconscious bias (manifestations), and the enduring consequences of (mis)trust in institutions (impact). The hourglass model can be used to inform operational tools, ensuring stigma is adequately addressed in outbreak preparedness and response activities.